Evaluation of total concentration and size distribution of bacterial and fungal aerosol in healthcare built environments. Issue 2 (April 2015) - Nasir, Zaheer Ahmad; Mula, Viswanath; Stokoe, Jane; Colbeck, Ian; Loeffler, Mark
This study aims to assess the levels and size distribution of airborne bacteria and fungi in two different types of orthopaedic theatres (conventionally ventilated and laminar flow), a general ward and outdoors in a hospital. The sampling was carried out with an Andersen six-stage viable impactor over a period of eight weeks. The highest mean concentration of total bacteria was found outdoors followed by the general ward, conventionally ventilated theatre and laminar flow theatre. With reference to Gram-negative bacteria, the general ward had the highest mean concentration followed by outdoors and the conventionally ventilated theatre. No Gram-negative bacteria were detected in the operating theatre with laminar flow. Similar to bacteria, the higher concentration of fungi was present outdoors and in the general ward as compared to the operation theatres. In general, higher concentrations were found in the conventionally ventilated theatre than the laminar flow theatre. In terms of size distribution, in the ward and outdoors the dominant bacteria, Gram-negative bacteria and fungi were in the size range of 3.3–4.7 µm or 2.1–3.3 µm. The bacterial concentrations in the conventionally ventilated operating theatre were mostly in coarse size fraction compared to fine fraction for the theatre with laminar flow.